2008
DOI: 10.1002/gj.1117
|View full text |Cite
|
Sign up to set email alerts
|

Pomeranian basin (NW Poland) and its sedimentary evolution during Mississippian times

Abstract: The Carboniferous sedimentary history of the Pomeranian Basin (NW Poland) begins with Hastarian open-marine carbonates and is terminated with ?lower Asbian terrestrial deposits in the north-eastern part and, ?upper Asbian or Brigantian, open-marine shales in the south-western part of the basin. The ?latest Viséan, Serpukhovian and early Bashkirian was a period of regional non-deposition and erosion. In the Upper Bashkirian-Gzhelian strata, an alluvial depositional environment was recognized.The Mississippian d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…On the southern margin of the Brabant Massif in Belgium, dolostone at the top of the Engihoul Formation is strongly karstified with depressions up to 15 m deep, and cavities filled with calcite replacements of selenitic gypsum growths and intercalations of crinoidal rudstone (Poty, ). In the Pomeranian Basin of north‐west Poland to the east, anhydrite beds and nodules are associated with black ‘shale’ and calcareous claystone of the upper Tournaisian Grzybowo Formation, deposited in a restricted lagoonal environment within a carbonate shelf setting (Matyja, ). A similar shallow marine and lagoonal setting in the Baltic region produced a succession of carbonate rocks with gypsum and siliciclastic rocks (Witzke, ).…”
Section: Discussionmentioning
confidence: 99%
“…On the southern margin of the Brabant Massif in Belgium, dolostone at the top of the Engihoul Formation is strongly karstified with depressions up to 15 m deep, and cavities filled with calcite replacements of selenitic gypsum growths and intercalations of crinoidal rudstone (Poty, ). In the Pomeranian Basin of north‐west Poland to the east, anhydrite beds and nodules are associated with black ‘shale’ and calcareous claystone of the upper Tournaisian Grzybowo Formation, deposited in a restricted lagoonal environment within a carbonate shelf setting (Matyja, ). A similar shallow marine and lagoonal setting in the Baltic region produced a succession of carbonate rocks with gypsum and siliciclastic rocks (Witzke, ).…”
Section: Discussionmentioning
confidence: 99%
“…The upper part of the Famennian and lower part of the Tournaisian deposits in the Pomerania area belong to the Sąpolno Calcareous Shale Formation (Matyja, 1993), which is a succession of open-marine carbonate and clayey deposits (Fig. 2a, b), formed below wave base and probably corresponding to a relatively shallow carbonate ramp environment (Matyja, 2006). The D/C boundary interval is marked, however, by monotonous, thin-bedded, dark grey marls, marly claystones and claystones, with only thin marly lime mudstone intercalations, which show a general absence of fauna (Matyja, 1993, 2009; Matyja & Stempień-Sałek, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…3), based on detailed core observations and geophysical logs we observed that the uppermost Famennian part of the section is more calcareous than the lowermost Tournaisian part, which is dominated by claystones.
Figure 2. Lithofacies pattern for the latest Famennian – earliest Tournaisian (a) and early Tournaisian (b) in northwestern Poland; modified after Matyja (2008, 2009).
Figure 3. Microfacies across the Devonian/Carboniferous boundary interval in the Chmielno–1 borehole section – an example of a monotonous succession where the Hangenberg Black Shale horizon is not developed; constituent grains as well as rock fabrics allow recognition of grey marls (Ch 64, Ch 58, Ch 53, Ch 52, Ch 51, Ch 49) and more or less marly limestones (Ch 63, Ch 50) with relatively high amounts of silt and organic matter.
…”
Section: Introductionmentioning
confidence: 99%
“…The Late Tournaisian pyro clastic or vol ca nic rocks were also re ported from sev eral places of the Trans-Eu ro pean Su ture Zone in Po land (see e.g., Narkiewicz, 2007). They oc cur within the Mid dle and Late Tournaisian sed i ments of Pomerania, the Łysogóry-Radom Block, the Małopolska Block and the Up per Silesian Coal Ba sin (Szulczewski et al, 1996;Muszyński et al, 1996;Narkiewicz, 2007;Matyja, 2008). At that time, re gional con ti nen tal ex tension in the shelf ba sin area trig gered wide spread magmatism, par tic u larly in tense dur ing the Late Tournaisian (see e.g., Krzemiński, 1999;Narkiewicz, 2007).…”
Section: Discussionmentioning
confidence: 99%